Innate immunity in the intestine in health and disease - Maloy, Kevin (Henry Stewart Talks, 2013)
Mucosal tissues of the human body, Intestinal pathogens, Mucosal immune system: distinctive features, Gut-associated lymphoid tissue (GALT), Structure of the GALT: small and large intestine, Mucus, a key protective barrier, Antimicrobial proteins protect the epithelium, Epithelial cell transcytosis of secretory IgA, Uptake and transport of antigen by M cells, Microbial sensing regulates intestinal homeostasis, Sensing of microbes occurs through PRR, MyD88 signals in IEC, Intestinal macrophages are anti-inflammatory, Intestinal DC 'conditioning', Inflammatory bowel disease (IBD), Genome-wide association studies, The enigma of NOD2 and Crohn's disease, NOD2 signaling in response to bacterial MDP, NOD2 signaling regulates myeloid cell function, Autophagy also regulates IEC and myeloid cells, MyD88 activation drives intestinal inflammation, Haematopoeitic MyD88 signals, Immune dysregulation in chronic inflammation, Innate lymphoid cells (ILC) drive innate IBD, Leukocyte populations and intestinal homeostasis